Outsomes of stroke patients discarged from an in-patient facility in the Eastern Cape, South Africa: a mixed methods design - N. Cunningham; A. Rhoda (AOSIS, 2014)
Statistics have indicated that stroke is a major health concern in the Eastern Cape Province in South Africa,